2020
DOI: 10.1136/bcr-2019-232970
|View full text |Cite
|
Sign up to set email alerts
|

Winged scapula following axillary thoracotomy with long thoracic nerve preservation

Abstract: Winged scapula is a rare condition caused by injuries to the long thoracic nerve (LTN) and accessory nerves. A 69-year-old man underwent surgery for right lung cancer. Video-assisted thoracic surgery was converted to axillary thoracotomy at the fourth intercostal space. The latissimus dorsi was protected, and the serratus anterior was divided on the side anterior to the LTN. Two months after discharge, he presented with difficulty in elevating his right arm and protrusion of the scapula from his back. Active f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Few studies have evaluated the incidence of postsurgical articular problems in patients undergoing thoracic surgery; however, the investigators did not assess the scapula. 16,[32][33][34][35][36] In the study of Miranda et al, 33 a marked reduction in shoulder ROM and disability after surgery was present in a short-term evaluation. Rodríguez-Torres et al 32 presented a more extended follow-up with a less incisive reduction in ROM and assessed muscular trigger points after VATS.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Few studies have evaluated the incidence of postsurgical articular problems in patients undergoing thoracic surgery; however, the investigators did not assess the scapula. 16,[32][33][34][35][36] In the study of Miranda et al, 33 a marked reduction in shoulder ROM and disability after surgery was present in a short-term evaluation. Rodríguez-Torres et al 32 presented a more extended follow-up with a less incisive reduction in ROM and assessed muscular trigger points after VATS.…”
Section: Discussionmentioning
confidence: 93%
“…The bibliographic literature search found few studies mentioning predictive factors or follow-up to clarify WS's incidence, risk factors, or prognosis after oncological thoracic surgery. 15,16,18 Moreover, we collected incidence data in neurological injury in robotic-assisted surgery, a new technique with few studies on postsurgical sequelae. 9 With a small amount of data available in the literature on thoracic surgery patients, our results are comparable only with previous studies in different populations, in which an incidence is reported of around 27% in breast cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of LTN dysfunction occurs as a result of closed trauma or following neuralgic amyotrophy as described by Parsonage and Turner (Kauppila & Vastamäki, 1996; Bizzarri et al, 2001; Isono et al, 2020). Despite advances in anatomical understanding, and the subsequent development of nerve‐sparing approaches and safe windows, there still remains a relatively high rate of iatrogenic injury to the LTN following shoulder, breast, and cardiothoracic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with bronchopleural fistula (BPF) due to complications of suppurative pleuropulmonary disease, along with medical treatments, surgical closure, including muscle flap, is performed to provide fistula coverage[ 6 ]. Axillary thoracotomy has a lower risk for muscle or nerve injury than the original thoracotomy, although there has been a case of injury to the intercostobrachial nerve or long thoracic nerve at the incision site or a very rare case of BP injury[ 7 , 8 ]. We report a patient who simultaneously suffered from BP injury, whole-division level, suprascapular nerve, and long thoracic nerve injury immediately following BPF closure surgery under general anesthesia in thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%